PENGARUH ALIH GUNA LAHAN SAWAH KE NON SAWAH TERHADAP PERUBAHAN MATAPENCAHARIAN DAN ASET KELUARGADI KECAMATAN BAWEN - Pitricia, Natalia; Hardati, Puji; Sanjoto, Tjaturahono Budi (Geo-Image, 2016)
The purpose of this study to determine the rate of agricultural land use (fields) to non-agriculture (paddy), the factors that influence the transfer of land use and the effects of changes in livelihoods and assets of farm households. The technique of collecting data through observation, questionnaires, interviews and documentation. Data analysis techniques in this study was the rate of transfer order, regression and descriptive percentage. The analysis showed that the rate of transfer to Bawen highest in the district occurred in 2007, which amounted to 24.65% and decreased again by 10.99% in 2010. The rate of transfer to the village Samban that is equal to 7.90%, while use change rate in Sub Harjosari ie 9.83%. This is due to a large industrial development in the region. Factors that affect the transfer of land use is agricultural land, land prices, the influence of neighbors, and the influence of the private sector / investors. Change the livelihoods of farmers before mostly in the agricultural sector, but after the transfer to the livelihoods of farmers in the non-agricultural sector, changes in livelihood assets also increased by an additional assets such as vehicles, electronic goods and other owned by utilizing quotient of profit they receive.